Coverage error in internet surveys: can fixed phones fix it? - Vicente, P.; Reis, E. (International Journal of Market Research, 2012)
The internet is increasingly being used for cross-sectional surveys and online panels. Although internet accessibility is growing across developed and developing countries, it seems unlikely that the internet alone will ever provide complete coverage of the general population. Given the incomplete coverage and imbalanced penetration rate of the internet across segments of the population, it is pertinent both for survey companies and academics to assess the potential of mixing the internet with other survey modes as part of a strategy to assure validity of inferential samples when surveying general populations. The purpose of this research was to evaluate to what extent coverage error in Internet surveys can be reduced by surveying the offline population via telephone. We use data from Eurobarometer collected in the EU27 member states to simulate first an internet-based survey and then a mixed-mode survey combining the Internet with the telephone. Comparisons are made to identify differences in the socio-demographic characteristics of internet households and those of non-internet households with telephone. Coverage error is also estimated in each survey design. Findings reveal significant socio-demographic differences and although the coverage error is reduced in the mixed-mode survey design, it cannot be completely eliminated. Moreover, the outcomes are not homogeneous across countries.